The role of dynamins and dynamin-related protein 1 (Drp 1) in the regulation of mitochondrial and peroxisomal fission. - Fonseca, Tiago Alexandre Branco (2017)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia